Placement Strategy for Officers Graduating from Sespimmen Polri Education in Their First Positions in Newly Formed Polda in Eastern Indonesia - Adho Ridwan; Asropi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study examines the placement strategy for officers graduating from Sespimmen Polri education in their first positions in newly formed regional police units (Polda) in Eastern Indonesia, with particular attention to Papua and other areas facing structural, geographical, and socio-cultural complexity. The formation of new Polda is intended to strengthen police services, shorten the span of control, and increase institutional responsiveness. However, personnel data indicate a persistent imbalance between the Personnel Structure List (DSP) and the actual availability of middle-level officers (RILL), especially in newly formed Polda that still require organizational consolidation. Using a qualitative descriptive-analytical approach, this study draws on interviews with human resource officials and Sespimmen graduates, supported by documentation on personnel needs, career development, and placement policy. The analysis shows that placement problems are caused by limited middle-level officer availability, suboptimal implementation of the merit system, weak integration between competency data and position analysis, rigid zoning policies, and the distinctive geographical and socio-cultural characteristics of Eastern Indonesia. The study argues that the first placement of Sespimmen graduates should not be treated as routine administrative rotation but as an institutional strategy based on DSP priority, regional vulnerability, competency mapping, Person-Organization Fit, adaptive zoning, and post-placement evaluation. Such a strategy is expected to improve leadership effectiveness, public service quality, and security governance in newly formed Polda in Eastern Indonesia.